Application of Safocid in clinical practice (review of the results of studies carried out in Russia) - A. A. Khryanin; O. V. Reshetnikov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
This systematic review presents the data on using the Safocid complex drug for the treatment of a combination or unknown pathology of the urogenital tract as well as for the prevention of pre- and post-surgical complications in case of urologic and gynecologic interventions. According to the review of 39 articles, the authors of most of the publications assess the drug efficacy as high while the amount of adverse effects is minimum.